Compound 48/80 acts as a potent mucosal adjuvant for vaccination against Streptococcus pneumoniae infection in young mice. Issue 8 (18th February 2015) - Zeng, Lingbin; Liu, Yusi; Wang, Hong; Liao, Pu; Song, Zhixin; Gao, Song; Wu, Yingying; Zhang, Xuemei; Yin, Yibing; Xu, Wenchun
Highlights Immunization with C48/80 enhances and maintains antigen-specific IgG in serum of young mice. C48/80 helps to clear nasal pneumococcal colonization via B cells and IL-17A. C48/80 induces greater protection against lethal pneumococcal infection than CT. C48/80 is a relatively safe adjuvant for young mice.